A educação matemática nos anos iniciais: análise de necessidades de formação profissional de docentes no contexto do SARESP - Barros, Regina Celia dos Santos Nunes [UNESP] (2014)
This research examined the possible relationship between the mobilized and declared by the teachers knowledge and their training needs relating to this knowledge with the prescribed training requirements in the proposed deployment EMAI Project - Management Education for the Early Years - in the context of evaluation system in large scale SARESP - evalution of Educational Achievement system of Sao Paulo. In this sense, the objective of this research was to investigate the possible relationship between the demands of EMAI design with the knowledge and training needs of teachers working in early years of elementary education in the context of SARESP. Therefore, the survey was conducted in four stages, with initiallity seek to know biodata of participants and their training course in Mathematics. In the second step we investigate how these teachers worked three activities present in the sequence of the 1st EMAI project for 3rd year; The third step was to investigate the relationship that teachers are among the activities EMAI worked with the questions proposed in the math test SARESP 3rd year of elementary school, held in 2012. Finally, in the last step, we wake a review about the considerations made in the previous steps. The study included a literature documents in the ESS / SP and other studies published in reputable journals with the intention of mapping studies that have addressed aspects of initial and continuing education of theachers in the early year of elementary education in the discipline of mathematical as well as EMAI characterize the design and evaluation on a large scale proposal annually to students belonging to basic education in the State of São Paulo, SARESP. Participee in this research, a qualitative one, two teachers acting in the early years of elementary of 3 s years teaching in a public school in São Paulo, that in situations of dialogue with the researcher, were invited to talk about their initial trainning and...